Association of Usual Sodium Intake with Obesity Among US Children and Adolescents, NHANES 2009‐2016. Issue 3 (2nd February 2021) - Zhao, Lixia; Ogden, Cynthia L.; Yang, Quanhe; Jackson, Sandra L.; Loria, Catherine M.; Galuska, Deborah A.; Wiltz, Jennifer L.; Merritt, Robert; Cogswell, Mary E.
Abstract : Objective: The purpose of this study was to investigate the association of sodium intake with obesity in US children and adolescents. Methods: Cross‐sectional data were analyzed for 9, 026 children and adolescents in the National Health and Nutrition Examination Survey (NHANES) 2009‐2016. Usual sodium intake was estimated from 24‐hour dietary recalls using a measurement error model. Logistic regression was used to assess the association of sodium intake with overweight/obesity, obesity, and central obesity (waist to height ratio [WtHR] ≥ 0.5; waist circumferences (WC) ≥ age‐ and sex‐specific 90th percentile). Results: Mean (SE) sodium intake was 3, 010 (9) and 3, 404 (20) mg/d for children and adolescents, respectively. The adjusted odds ratio (AOR) comparing Q4 versus Q1 (87.5th vs. 12.5th percentile of sodium intake) among children was 1.98 (95% CI: 1.19‐3.28) for overweight/obesity, 2.20 (1.30‐3.73) for obesity, 2.10 (1.12‐3.95) for WC ≥ 90th percentile, and 1.68 (0.95‐2.97) for WtHR ≥ 0.5, adjusting for demographics, energy, and sugar‐sweetened beverage intake. Among adolescents, AOR was 1.81 (0.98‐3.37) for overweight/obesity, 1.71 (0.82‐3.56) for obesity, 1.62 (0.71‐3.66) for WC ≥ 90th percentile, and 1.73 (0.85‐3.50) for WtHR ≥ 0.5. Conclusions: Sodium intake was positively associated with overweight/obesity, obesity, and central obesity among US children independent of energy and SSB intake, but the association did not reach significance among adolescents.